The internet as a marketing environment: consumer perceptions, attitudes and behavior - Kımıloğlu (Türker), Hande Bahar. (Thesis (Ph.D.) - Bogazici University. Institute of Social Sciences, 2001., 2001)
In this dissertation, we aim to discover consumers' perceptions of, attitudes toward, intentions about the usage and behavior on the Internet as a decision making and purchasing environment. One major objective of the study is to draw a general profile of Internet consumers. Although we have encountered attempts to disclose the demographics of the online consumer community, an overall picture consisting of both demographic and psychographic attributes is an important contribution we can make to the literature. The other objectives of the study are to provide an understanding of some of the contextual factors preceding the formation of consumers' dispositions toward and actual behavior on the virtual marketplace, to demonstrate consumers' perceptions about the characteristics of the Internet as a marketing environment, to determine the suitability attributed to the performance of different stages of the purchasing process in this medium, to assess the potential it carries for different types of products and services, and to identify consumers' perceptions about current and future usage and adoption levels. In the introduction, prominent issues about online consumer behavior have been explored and information is provided about how the Internet changed the world of marketing, how it challenged established theories, and what the most conspicuous differences between traditional and contemporary marketing practices are. Then, a comprehensive review of the literature has been presented. In this section, a framework that serves as a guideline to categorize the major titles and subtitles of the topic has been constructed. We expect this cla<;sification to reveal the numerous research avenues available about the subject and to disclose the missing spots that need to be investigated further. As for the theoretical base the study lies on., a comprehensive model including a conglomeration of the variables expected to affect the consumer-Internet encounter is constructed. After touching upon how each variable fits into the model, a selected part of it has been used for empirical purposes. The research methodology employed rests on a questionnaire that has been carefully designed and tested with a pilot study before application. The data collection instrument has been directed toward 503 members of the Turkish online community who are potential and actual users of the Internet as a decision making and purchasing environment SPSS 10.0 has been used for the statistical part of the study. Cross-tab, Pearson correlation., T -Test, OneWay ANOV A, regression and discriminant analyses have been performed for testing our hypotheses. Our findings suggest that the Internet is, yet, quite a novel environment for consumer decision making and purchasing activities. However, expectations about its future state are very positive indicating a high potential of growth especially for certain sectors. StiU, the Internet is apt to become one of the attractive marketing media among many others available to consumers and businesses rather than a development that eliminates traditional shopping channels and structures as a whole. It is currently preferred more extensively for informational and comparative purposes. Although consumers have developed positive perceptions about the major advantages of this medium, they have certain concerns toward the disadvantages it possesses, too. Finally, in light of the various interesting and original findings that we have obtained, numerous implications have been proposed for online and offiine businesses, consumers, governments and legal authorities, Internet service providers and for further research. In short, this study makes considerable contributions to the relevant literature by providing a theoretical framework that proposes a model to understand online consumer behavior and also utilizing the model for practical purposes, too.
Keywords: Internet marketing.; Consumer behavior.; Electronic commerce.